2008
DOI: 10.1002/xrs.1026
|View full text |Cite
|
Sign up to set email alerts
|

PIXE and ionoluminescence for Mesoamerican jadeite characterization

Abstract: Greenstones were highly appreciated in pre‐Hispanic Mesoamerica. Most of the finest green artifacts were worked in jadeite and other minerals such as serpentine and nephrite. Jadeite, the most precious stone in ancient Mesoamerica, was widely used and traded since the Preclassic Horizon (1500 B.C.). The main beds are located in the Maya region, in the Motagua area of Guatemala. In this work, three pieces of a necklace of greenstones from an offering (corresponding around 155 A.D.) discovered in an extensive ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…It is a sensitive and versatile tool for study of excitation states of the material, local symmetry of the emitting atom, chemical state and presence of RE ions [8]. IL studies have been reported on various types of natural and synthetic inorganic materials [9][10][11][12]. The objective of the present work is to study ion induced luminescence characteristics of Y 2 The ratio of citric acid to Y 3 þ is considered as 2.0 [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It is a sensitive and versatile tool for study of excitation states of the material, local symmetry of the emitting atom, chemical state and presence of RE ions [8]. IL studies have been reported on various types of natural and synthetic inorganic materials [9][10][11][12]. The objective of the present work is to study ion induced luminescence characteristics of Y 2 The ratio of citric acid to Y 3 þ is considered as 2.0 [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The ruling elite of Teotihuacan controlled raw materials that came from afar: jadeite from the Motagua region in HondurasGuatemala, and mica from the central valleys of Oaxaca, as seen in palatial structures such as Xalla (51,59,60), but the intermediate elites were highly active in providing a wide range of other sumptuary goods to Teotihuacan society: pigments, cosmetics, slate from different sources, greenstones, travertine, limestone, flint, and foreign pottery.…”
Section: Discussionmentioning
confidence: 99%
“…Elemental contents were quantitatively determined using PIXE spectrometry on the external proton beam of 3 MeV at our Tandem Pelletron Accelerator facility . A laser pointer system and a high‐resolution color camera help to set the sample in front of the beam on the selected regions using an X–Y translation stage.…”
Section: Methodsmentioning
confidence: 99%